Virtual Lab to run experiments of oscillations of a stretched rectangular membrane - Montenegro Joo, Javier (2017)
A Virtual Lab to run educational computer simulations of a vibrating membrane has been created. This educational virtual lab may be used to support some courses in the vibration engineering career. The module solves the 2D wave equation for a rectangular membrane which is shown on computer-screen vibrating according to data supplied by the user. The Virtual Lab makes the computations and renders on screen a 3D view of the vibrating membrane, which displays the normal modes of oscillation. A short theory is shown on screen while the simulation takes place, in this way the learning is fostered because the user verifies the theory with the simulation. Details on how to develop the simulation program are included, so that interested readers may create their own simulators. Some comments about the advantages of using computer simulation in education are included.